PENGARUH MEDIA ANIMASI TERHADAP KETERAMPILAN MENDENGAR BAHASA JERMAN SISWA KELAS XI SMA YP HKBP PEMATANGSIANTAR - Novriana Damanik; Yanti Arasi Sidabutar; Insenalia Sampe Roly Hutagalung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of animated media on the German listening skills of grade XI students at YP HKBP Pematangsiantar High School. This study is a quantitative study with a pre-experimental research design and a one-group pretest-posttest design. The research instrument used a multiple-choice test consisting of 25 questions. After conducting data analysis techniques, the pretest mean score was 43.8 and the posttest mean score was 87.3. The research sample was class XI-3 with a total of 34 students. Based on the hypothesis testing results using the T-test and N-Gain test, the T-test analysis showed a value of 25.669, while the df level was 33, resulting in a value of 2.034. Therefore, is accepted and is rejected. Based on the N-Gain percentage score N-Gain percentage score of 77.2%. Therefore, it can be concluded that there is an effect of animation media on the German listening skills of students in class XI at SMA YP HKBP Pematangsiantar.